Improving Competence across the Lifespan Building Interventions Based on Theory and Research - Pushkar, Dolores.; Bukowski, William M.; Schwartzman, Alex E.; Stack, Dale M.; White, Donna R. (Springer US, 2002)
This book arises from a conference held in November 1996 designed to examine how competence can be improved in the different stages ofthe lifespan. To this end, we brought together eminent researchers in different areas of human developmentỚ infancy, childhood, and adulthood, including the late adult years. The conference was based on the premise that discussion arising from the interfaces of research and practice would increase our knowledge of and stimulate the further application of effective interventions designed to improve competence. The editors wish to acknowledge the contributions of Concordia University and the Fonds pour la Formation de Chercheurs et lỚ"Aide a la Recherche (FCAR) in providing funding and other assistance toward the conference ỚSImproving Competence Across the LifespanỚ<U+00fd> and toward the publication of this book. Finally, we wish to express our gratitude to the numerous students associated with our Centre for their help and to Gail Pitts and Lesley Husband of the Centre for Research in Human Development for their assistance. We are especially grateful to Donna Craven, Centre for Research in Human Development, for her heroic work on both the conference and the present volume. We could not have met our goals without you.